O imenicama koje završavaju sufiksoidom -cid - Šešum, Andrea (Slavistična revija, 2025)
In the Bosnian, Croatian, and Serbian language standards, there are words ending with the suffixoid -cid, which is actually an allomorph of the root -cid from the Latin verbs caedo, 3., cecidi, caesum, meaning “to cut”, “to chop”, “to strike”, “to whip” and occido, 3., occisi, occisum, meaning “to kill”. In previous linguistic research, there was no particular interest in analyzing this suffixoid, while in Slavic languages there is no unique native suffix to denote killing or destruction, which is why the process of borrowing terminological lexicon began. The aim of this study is: 1. to identify words ending with the suffixoid -cid in dictionaries of the three standards; 2. to define the meanings of those words ending with -cid that are not part of the existing dictionary stock; 3. to determine their frequency in electronic corpora on the CLARIN platform. Keywords: loanwords, adaptation, word origin, hybrids, terminological lexicon
Keywords: adaptacija; adaptation; besedoslovje; bosanščina; Bosnian language; Croatian language; hibridi; hrvaščina; hybrids; izposojenke; izvor besede; lexicology; loanwords; Serbian language; srbščina; terminological lexicon; terminološka leksika; word origin